EMSY links the BRCA2 pathway to sporadic breast and ovarian cancer. - Hughes-Davies, L; Huntsman, D; Ruas, M; Fuks, F; Bye, J; Chin, S; Milner, J; Brown, L; Hsu, F; Gilks, B; Nielsen, T; Schulzer, M; et al. (2003)
The BRCA2 gene is mutated in familial breast and ovarian cancer, and its product is implicated in DNA repair and transcriptional regulation. Here we identify a protein, EMSY, which binds BRCA2 within a region (exon 3) deleted in cancer. EMSY is capable of silencing the activation potential of BRCA2 exon 3, associates with chromatin regulators HP1beta and BS69, and localizes to sites of repair following DNA damage. EMSY maps to chromosome 11q13.5, a region known to be involved in breast and ovarian cancer. We show that the EMSY gene is amplified almost exclusively in sporadic breast cancer (13%) and higher-grade ovarian cancer (17%). In addition, EMSY amplification is associated with worse survival, particularly in node-negative breast cancer, suggesting that it may be of prognostic value. The remarkable clinical overlap between sporadic EMSY amplification and familial BRCA2 deletion implicates a BRCA2 pathway in sporadic breast and ovarian cancer.